Disparities in Patient- and Family-Centered Care Among Children With Health Conditions. (April 2022) - Kindratt, Tiffany B; Lark, Payton; Ray, Madison; Brannon, Grace Ellen
The objective of this study was to estimate and compare the prevalence of patient- and family-centered cae (PFCC) received by children in the United States (US) with chronic and developmental health conditions and determine associations between the presence of the conditions and parents' perceptions of PFCC after controlling for covariates. Linked data from the 2012–2016 National Health Interview Survey (NHIS) and 2013–2017 Medical Expenditure Panel Survey (MEPS) (n = 7, 835) were tested using crude and adjusted logistic regression procedures. Parents of children with developmental delays had 32% lower odds (95% CI = 0.51–0.90) of reporting their healthcare provider always exhibited all PFCC qualities. Parents of children with allergies and developmental delays had 26% (95% CI = 0.58–0.95) and 42% (95% CI = 0.42–0.80) lower odds of reporting their provider always listened carefully compared to parents whose children did not. Findings demonstrate the importance of continuous training for providers to tailor communication for families who have children with health conditions.